Societal Reactions to Suicide in Ghana: A Qualitative Study of Experiences of the Bereaved - Osafo, J.; Andoh-Arthur, J.; Knizek, L.B.; Hjelmeland, H. (The Journal of Crisis Intervention and Suicide Prevention, 2019)
Background: Condemnatory reactions toward suicide are prevalent in Africa, yet no study has examined how society reacts to suicides from the perspective of suicide-bereaved persons. Aims: This qualitative study explored societal reactions to suicides so as to further our understanding of the problem in Ghana. Method: Using a semi-structured interview guide, we interviewed 45 close relations of 14 men who took their lives. Results: The reactions followed ontological questions of what suicide means (construing the act), its impact (consequences), why it happened and who to blame (attributions and allocation of responsibility), and how to remedy perceived damages (damage control). Limitations: Focusing on suicides of only men might have limited the range of societal reactions to suicide in general. Conclusion: Reparative and retributive societal reactions to suicides were influenced predominantly by views that suicide is an extraordinary moral evil in the setting. Increased culturally focused suicide education can improve people's understanding and enhance responsive suicide prevention and postvention
Research Article
Keywords: societal reaction; suicide; suicide-bereaved; Ghana